Characterization of Acrylonitrile Butadiene Styrene for 3D Printed Patch Antenna - Norun Abdul Malek; Athirah Mohd Ramly; Atiah Sidek; Sarah Yasmin Mohamad (Institute of Advanced Engineering and Science, 2017)
3D printing is one of the additive manufacturing technology that has gain popularity for time saving and complex design. This technology increases a degree of flexibility for potential 3D RF applications such as wearable and conformal antennas. This paper demonstrates a circular patch antenna fabricated on 3D printed Acrylonitrile Butadiene Styrene (ABS) filament. The main reason of using a 3D printer is that it is accurate, easy to fabricate of a complex geometry and the ability to create new antennas that cannot be made using conventional fabrication techniques. The ABS material has a tangent loss of 0.0051 and the relative permittivity is 2.74. The thickness of the substrate is 1.25 mm. The simulation has been performed using Computer Simulation Technology (CST). The return loss from simulation software is in good match with measurement which is 12.5dB at 2.44GHz. Hence, from the results obtained, the ABS could be used as a substrate for an antenna.